PENGARUH FAKTOR-FAKTOR EKSTERNAL TERHADAP KEPUTUSAN PEMILIHAN BANK - Nurus Sobakh (Jurnal Keuangan dan Perbankan, 2008)
This study was in term of survey, with the purpose to find out the effect of externalfactors comprising culture, social level, reference group, family, and economic condition towardthe decision in selecting bank. The population of this study was all customers of Tahapan BCAin PT. BCA, Tbk, KCP Dinoyo Malang, namely 25,478 persons, meanwhile the samples takenwere 73 persons with accidental sampling; data collection techniques were questionnaire andmultiple regression data analysis technique.The result of the study concluded that externalfactors comprising culture, social level, reference group, family, and economic conditioninfluenced the decision in selecting bank, either partially or simultaneously, and independentsub-variable or economic condition had dominant effect and biggest contribution toward thedecision in selecting bank, compared with another independent sub-variable. Meanwhile thesuggestion provided dealing with the conclusion above was that PT. BCA, Tbk, KCP DinoyoMalang should have made closer relationship with the customers and society in order to perceivebuying behavior, in order to be able to formulate right and efficient marketing strategy thatin turn would add the number of customers.